Analisis Metabolomik pada Interaksi Padi dan Bakteri: Metabolomics Analysis on the Interaction of Rice and Bacteria - Theowidavitya , Brian; Muttaqin, Mafrikhul; Miftahudin; Tjahjoleksono, Aris (Departemen Biologi, Institut Pertanian Bogor, 2019)
Mutualistic plant-microbe interaction can increase the availability or absorption of nutrients and affect plant metabolism. Metabolomics is the study of all metabolites contained in living beings at a specific time. This research aims to study the effect of metanotrophic bacteria (BGM 9 isolate) and nitrogen-fixing bacteria (ITJ 7 isolate) on rice plant growth and reveal the information about metabolites produced by rice plant interacting with the bacteria. Three rice plant varieties (Ciherang, Hawara Bunar, and IR64) were grown on liquid media (Yoshida solution) and were inoculated with the bacteria five weeks after planting. Metabolites in the liquid media were detected seven days after inoculation using Liquid Chromatography-Mass Spectrometry and analyzed using MassLynx v4.1. The results showed that the bacterial inoculation had significant effect on rice growth. Chromatograms resulted from LC-MS showed there are 34 unique peaks from Ciherang, 21 unique peaks from Hawara Bunar, and 30 unique peaks from IR64. The unique peaks in each variety were affected by the bacteria inoculation treatments.